Saneamento no Brasil: proposta de priorização do investimento público - Kuwajima, Julio Issao,Santos, Gesmar Rosa dos,Fechine, Valéria Maria Rodrigues,Santana, Adrielli Santos de (Instituto de Pesquisa Econômica Aplicada, 2020)
Based on the acknowledged importance of the State actions in water supply and sewage services, this article aims to present a methodological proposal for prioritizing public investment in this area. Therefore, based on the attributions applied in the legislation, Brazilian municipalities were classified based on a set of indicators, and classification groups of priorities were created, in order to balance the conditions of access to public financial resources. It is, also considered that the improvement of the allocation of Union resources in the sector, through times of fiscal crisis, must follow the requirement that meet the risks in the situation of greater social vulnerability and municipalities with greater deficits. As a result, are listed 961 municipalities with top priority and second priority degrees, as well as two other groups with precarious water or sanitation services that must be considered, benefiting 35.7 million inhabitants. It is also pointed out additional suggestions with complementary meaning, such as investment actions and integrated management policies related to this theme.
10.38116/td2614
Keywords: Graue Literatur; safe water; sewage; investment; priorities; deficit; vulnerable population